Relationship between Knowledge and Preventive Behavior of Leptospirosis in Berbah District Sleman Regency Yogyakarta in 2021 - Murwani, Arita; Ashar, Hadi; Apriningtyas Budiyati, Gani (Institute of Topical Disease Universitas Airlangga, 2022)
Public Health is the resultant from an balance of individual, agent, and environment problems. Individual knowledge and the ability to adapt to the environment vary greatly. The individual awareness and sensibility towards surroundings will contribute to the public health status. Environmental factor in the raining season with high intensity of rainfall cause some risks such as flood. It can be a disaster and destroy the facilities in the area. This can be a transmission media, a new habitat of insects for certain disease, one of them is Leptospirosis. The condition after flood with low level of clean water facilities can make these bacteria live and reproduce, with warm temperatures, neutral pH of water, humidity and also high rainfall. Leptospirosis cases in Indonesia are sufficiently high which in 2019, there are 845 cases with mortality rate for 16.26%. Some factors may affect the number of the case. This research is aimed to know the factors related to the preventive behavior of leptospirosis. It was held in Public Health Center Berbah Yogyakarta. The method of research is quantitative research with design survey method, quasi experiment. The population is the clients visiting to Public Health Center Berbah, with the average number of clients coming are 200 clients/day. The sample is taken by accidental sampling to the clients with the number of daily visits (50 persons). The result shows, that of five analyzed factors, knowledge is the factor related to the preventive behavior of leptospirosis.